An overview of processes and considerations in the modelling of fixed-bed biomass combustion. (August 2015) - Khodaei, Hassan; Al-Abdeli, Yasir M.; Guzzomi, Ferdinando; Yeoh, Guan H.
Abstract: Biomass fuel is an environmentally friendly renewable energy source and carbon-neutral (non-fossil) fuel alternative. To facilitate its wider uptake, significant efforts are undertaken to model and experimentally study biomass combustion processes, in both industrial-scale (grate fired) and small-scale (lab-scale) combustors. In many studies, the core aim is to better understand the relationship between thermal conversion processes (drying, pyrolysis, char conversion) and their interrelationship to combustor performance (efficiency, emissions, process temperatures, scale formation, and instabilities). However, due to the complexity of solid fuel (particle) conversion and fuel bed behaviour, precise modelling of all aspects of biomass fixed-bed combustion is not readily achievable. Despite the existence of excellent experimental and modelling studies on numerous aspects related to the characteristics of forestry derived biomass fuels and their combustion, research in this field is challenging. Complications arise from the multitude of fuels used, the varying geometries and combustor configurations investigated and the different modelling methodologies adopted to resolve steady-state and transient operation. The literature includes works on various aspects of biomass combustion, including that undertaken in fixed-beds. However, whilst these works are valuable, they do not sufficiently cover the methods and fundamentals to model direct thermal conversion, at the bed and particle-level. The aims of the present study are to provide a fundamental overview of the methodologies employed in the modelling of laboratory-scale fixed-bed combustors. The paper also includes treatment of the fundamental thermo-physical fuel characteristics which need to be considered when undertaking macro-scale (bed-level) modelling. The paper concludes with summary observations in relation to the modelling of fixed-bed combustion as well as some opportunities which warrant further research and the challenges to be overcome. Highlights: Overview into thermal conversion of biomass in fixed-bed combustors. Review of experimental, theoretical and modelling approaches. Modelling of bed and particle-level processes (mathematical and CFD). Expressing combustion performance (emissions, thermal conversion efficiency). Summary of opportunities, achievements and outstanding challenges given.